Analisis Flavonoid Total dan Aktivitas Antioksidan Fraksi Etanol Kulit Semangka (Citrullus lanatus) - Feronika Evma Rahayu; Dede Irma Hidayat; Tunas Alam (Fakultas Farmasi Universitas Setia Budi, 2024)
Antioxidants are required to keep the body's defenses against free radicals intact. Watermelon rind (Citrullus lanatus (Thunb). & Nakai) contains phenolic compounds which are included in the flavonoid group and can act as natural antioxidant compounds. This study evaluated watermelon rind (Citrullus lanatus (Thunb). & Nakai) for its antioxidant activity. The dried watermelon rind (Citrullus lanatus (Thunb). & Nakai) was extracted using the maceration method and then partitioned into polar (water), non-polar (n-hexane), and semi-polar (ethyl acetate) fractions. Following extraction, the study's methodology is briefly outlined in the second paragraph and is in line with the findings of this publication. The highest total flavonoid value was found in the watermelon rind (Citrullus lanatus (Thunb). & Nakai) ethanol extract, which measured 49.6 mg/g in the ethyl acetate fraction, 48.6 mg/g in the water fraction, and12.05 mg/g in the n-hexane fraction. The ethyl acetate fraction has strong antioxidant activity (55.36), followed by the water fraction (71.25), and the n-hexane is not strong (225.59).